PENERAPAN METODE ASSOCIATION RULE PADA DATA IKLAN GOOGLE ADWORDS BERDASARKAN POLA PENAYANGAN IKLAN (STUDI KASUS: OKE WEB INDONESIA) - Yuli Febyola (2022)
Advertising is a form of information technology development that is used by companies to promote sales products. Google AdWords advertising is one of the new platforms to provide information and has a persuasive nature to attract customers, and can optimize business people to introduce their products with a broad scope. In this case, research was conducted to find new rules on Google AdWords advertising data using apriori algorithm data mining techniques. This research has benefits for companies to get a marketing strategy for serving Google AdWords ads based on the rules that are formed. The data used in this study were obtained from Oke Web Indonesia, with the object of research being car advertising products. This study uses a minimum support parameter value of 30% and a minimum confidence value of 50% which is applied to the data of 11 car brands. The results of the a priori algorithm calculations in this study produce rules on car advertising products that are most in demand by customers, namely Honda, Wuling, Hino, and KIA.